Unified framework based parallel FEM code for simulating marine seismoacoustic scattering - Jirong, Shen; Shaolin, Chen; Jiao, Zhang; Puxin, Cai (Frontiers in Earth Science, 2023)
The simulation of seismic wave propagation in the sea area, which belongs to seismoacoustic scattering problem, is complicated due to the fluid-solid interaction between seawater and seabed, especially when the seabed is saturated with fluid. Meanwhile, huge computation resources are required for large-scale marine seismic wave simulation. In this paper, An efficient parallel simulation code is developed to solve the near-field seismoacoustic scattering problem. The method and technologies used in this code includes: (1) Unified framework for acoustic-solid-poroelastic interaction analysis, in which seawater and dry bedrock are considered as generalized saturated porous media with porosity equals to one and zero, respectively, and the coupling between seawater, saturated seabed and dry bedrock can be analyzed in the unified framework of generalized saturated porous media and avoid interaction between solvers of different differential equation; (2) Element-by-element strategy and voxel finite-element method (VFEM), with these strategies, it only needs to calculate several classes of element matrix and avoid assembling and storing the global system matrices, which significantly reduces the amount of memory required; (3) Domain-partitioning procedure and parallel computation technology, it performs 3D and 2D model partitioning for the 3D and 2D codes respectively, sets up the velocity structure model for the partitioned domain on each CPU or CPU core, and calculates the seismic wave propagation in the domain using MPI data communication at each time step; (4) Local transmitting boundary condition, we adopt multi-transmitting formula, which is independent of specific wave equations, to minimize reflections from the boundaries of the computational model. A horizontal layered model with the plane P-wave incident vertically from bottom is used to demonstrate the computational efficiency and accuracy of our code. Then, the code is used to simulate the wave propagation in Tokyo Bay. All codes were written following to the standards of Fortran 95.